Seasonal variation of δ13C content in Porites coral from Simeulue Island waters for the period of 1993-2007 - Sri Yudawati Cahyarini (Geological Agency, 2014)
DOI: 10.17014/ijog.v1i2.179Variation of δ13C content in coral skeletons shows the influence of metabolic fractionation in aragonite coral. Understanding coral δ13C variation can thus be useful to more understand e.g. past bleaching event which is further useful for coral health and conservation. In this study, δ13C content in Porites coral from Labuhan Bajau, Simeulue Islands was analyzed. To know the correlation between variation of coral δ13C and light intensity, the monthly variation of coral δ13C is compared to solar radiation and cloud cover. The result shows that for the period of 2003 to 2008, coral δ13C shows it is well correlated (r=0.42 p=0.153) with cloud cover variation in annual mean scale. Meanwhile, in seasonal mean variation, coral δ13C is strongly influenced (r=0.85 p<0.0001) by cloud cover with 1 - 2 month time lag. Comparing to the solar radiation (cloud cover), SST influences dominantly the variation of coral δ13C from southern Simeulue Island waters (LB sample) in an annual mean scale than in a seasonal scale.